Jawetz, Melnick & Adelberg Microbiología Médica - Riedel,Stefan; Hobden, Jeffery A.; Miller, Steve; Morse, Stephen A.; Mietzner, Timothy A.; Detrick, Barbara; Mitchell, Thomas G.; Sakanari, Judy A.; Hotez, Peter; Mejia, Rojelio (McGraw-Hill's AccessMedicina., 2020)
The twenty-eighth edition of Jawetz, Melnick, and Adelberg's Medical Microbiology remains true to the objectives of the first edition published in 1954, which is to "provide a brief, concise, and updated of those aspects of medical microbiology that are of particular significance for the field of clinical infections and chemotherapy ".